Analisis Faktor-Faktor Yang Mempengaruhi Tingkat Kesejahteraan Masyarakat Kabupaten Jeneponto - Nur Aisyah Qadri Saiful (Universitas 45 Surabaya, 2023)
Welfare is closely related to the goals of the Indonesian State. The state is established, maintained and developed for the benefit of all the people, namely to guarantee and advance the general welfare. Low income means that people cannot access education and health due to limited costs. Based on this background, this research was conducted with the title